2020
DOI: 10.1128/msphere.00654-20
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Variable Domain 4 Linear Epitopes of theChlamydia trachomatisMajor Outer Membrane Protein Are Not Associated with Chlamydia Resolution or Reinfection in Women

Abstract: Chlamydia trachomatis is an obligate intracellular bacterium. C. trachomatis infection is the most prevalent bacterial sexually transmitted infection and can lead to pelvic inflammatory disease and infertility in women. There is no licensed vaccine for C. trachomatis prevention, in part due to gaps in our knowledge of C. trachomatis-specific immune responses elicited during human infections. Previous investigations of the antibody response to C. trachomatis have identified immunodominant antigens and antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
(61 reference statements)
3
14
0
Order By: Relevance
“…Short (6-15 amino acid) random peptide insertions at this site are highly compatible with VLP assembly and are displayed multivalently on the VLP surface ( 54 , 55 , 69 ). VLPs with specific binding characteristics can be affinity selected from large libraries of VLPs displaying random peptides using, for example, mAbs ( 71 , 72 ) or polyclonal IgG ( 73 , 74 ). We generated nine independent VLP libraries (displaying random 6-, 7-, 8-, 9-, 10-, 11-, 12-, 13-, & 15-amino acid inserts, respectively) using methods established previously ( 54 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Short (6-15 amino acid) random peptide insertions at this site are highly compatible with VLP assembly and are displayed multivalently on the VLP surface ( 54 , 55 , 69 ). VLPs with specific binding characteristics can be affinity selected from large libraries of VLPs displaying random peptides using, for example, mAbs ( 71 , 72 ) or polyclonal IgG ( 73 , 74 ). We generated nine independent VLP libraries (displaying random 6-, 7-, 8-, 9-, 10-, 11-, 12-, 13-, & 15-amino acid inserts, respectively) using methods established previously ( 54 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Human serum samples. Collection and use of human serum samples was approved as previously described [12] by the University of Alabama at Birmingham Institutional Review Board, the Jefferson County Department of Health (JCDH) in Birmingham, AL, USA, and the University of New Mexico Health Sciences Center Human Research Review Committee. Participants were enrolled from two populations: (1) predominantly African-American C. trachomatis-infected women aged >16 years presenting to the JCDH STD Clinic in Birmingham, AL, USA, and (2) Hispanic and non-Hispanic white virgin women aged 18-40 years presenting for routine gynecologic examinations in Albuquerque, NM, USA.…”
Section: Methodsmentioning
confidence: 99%
“…In a clinical trial, the MOMP-VD4 CTH522 vaccine was shown to be safe and immunogenic in 15 women, inducing neutralizing antibody in serum after three intramuscular injections, though MOMP-specific IgG and IgA were less prevalent in mucosal secretions and not shown to be neutralizing [8]. As with vaccination with CTH522, genital infection with C. trachomatis induces a robust antibody response against MOMP-VD4 [11,12]. However, this response is not protective: re-infection with the same C. trachomatis serovar is common [13] and not associated with the quantity or quality of the MOMP-VD4 antibody response [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected population was analyzed by Ion Torrent sequence analysis, allowing creation of a profile representing the various linear epitopes recognized by antibodies in infected individuals. We have extended the method to other viral and bacterial pathogens, including Zika virus (unpublished) and Chlamydia trachomatis [ 24 ].…”
Section: Antigen-fragment Librariesmentioning
confidence: 99%